Challenges Facing the Directorate of Criminal Investigation On Management of Criminal Gang Activities in Nairobi County, Kenya - Egesa Natwoli, Robert (Advances in Social Sciences Research Journal, 2021)
Abstract This paper uses data collected for an MA Thesis on the challenges facing the Directorate of Criminal Investigation Department on management of criminal gang activities, in Nairobi County, Kenya. This study has been necessitated by continued concern among policymakers, security pundits and citizens about the rising criminal gang activities in the country, more pertinently in Nairobi County. Although there are few studies that tried to scratch this area, there has never been a detailed and systematic inquiry and analysis of this problem. The study was guided by several specific objectives; the first objective examined the tactical challenges that the police face in policing gang related activities in Nairobi County, Kenya; assessed the effect of corruption in undermining the war against gang related activities in Nairobi County, Kenya; and finally explored other technological challenges that the police face in policing gang related activities in Nairobi County, Kenya. The study adopted descriptive research design and purposive sampling technique to collect data. Interview schedules and key informants (K.I) guide were the main tools used to collect data using the interview method of data collection. 60 officers of the Special Crime Prevention Unit were the main respondents. Major challenges faced by the DCI officers when dealing with criminal gang activities especially within Nairobi County include; poor relationship between police and the general public as reported by 89.1% of the respondents, increased involvement of women in gang activities which is exacerbated by low ratio of female-male officers for undercover operations and 90.9%. of respondents indicated due to woman innocence will create a greater challenge. Others include; gang related activities with networks and markets especially for stolen vehicles across the borders as a result of corruption along the borders by both police, custom and military officers. Further, 85.5% indicated that cross border gang activities were worsened by lack of harmonized law for the regulation and prevention of these activities that led to enhanced proliferation of weapons as well as drugs to and from the neighboring countries. Major recommendations for policy considerations included; increased recruitment and deployment of female officers to beef up their ratio in undercover operations. Harmonized laws for the neighboring East African community countries and increased cooperation between the security organs of these countries in order to have a coordinated approach of tracking and apprehending criminals who escape to neighboring countries. The study also recommends mandatory training for DCI officers in computer/ technological skills to be able to intercept, interpret and or decode gang related communication and cybercrime related activities.